Preservation of Urban Historic Centers. (2016) - Bezrodny, Konstantin; Lebedev, Mikhail; Larionov, Roman
Abstract: The subway construction in St. Petersburg is a very important challenge for the development of the city. The existing stations are dramatically deficient, especially in the city's bedroom suburbs. The end stations are overloaded, and parallel subway lines have to be built to relieve the available ones. The subway in St. Petersburg is mainly a deep-level one, as stable water-free rocks (Proterozoic clays) are at depths of over 40 m. Located higher are unstable aqueous sand-clay Quaternary varieties prone to frost heave, and parent Upper Vendian clays, characterized by fissures and sandstone interbeds of varying thickness. But even at significant bore depths, ground surface movements occur on large areas covering several hectares of the city's territory. The current technology of construction of subway station hubs and inclined escalator tunnels lead to significant deformations of the overlying rock and of buildings and structures erected on it, sometimes resulting in loss of structural strength and full decommissioning of buildings. The rehousing of dangerous buildings and their repair require sizeable funds and time for reconditioning of the buildings. This is especially intolerable for subway construction in the historic center of the city when memorial buildings and samples of architecture are subjected to total destruction. For instance, during the construction of the exit to the Griboyedov Canal from Nevsky Prospekt Station, one half of a historic building was dismantled, and for the construction of the surface concourse of Admiralteiskaya Station, an available house had to be totally pulled down, with a new one having similar facades erected in its place later. Therefore, extremely important is development and implementation of proposals to prevent intolerable deformations of existing buildings and structures in the construction of the subway and other underground facilities in the central districts of St. Petersburg. To solve the problem of ground surface deformation, an integrated approach is needed, comprising low-subsidence sinking techniques with parallel geotechnical monitoring including monitoring of low-depth displacements of the surrounding rocks, both in the vertical and horizontal plane.